Current research trends, hotspots, and frontiers of medical nutrition therapy on cancer: a bibliometric analysis - Xia, Hongfang; Wang, Liang; Wang, Haihua (Frontiers in Oncology, 2023)
Background: There is a high prevalence of malnutrition in cancer patients, which seriously affects the anti-cancer therapy effect and outcomes, causing a huge disease burden worldwide. The aim of this study was to explore the development trends, hotspots, and frontiers of Medical Nutrition Therapy (MNT) on Cancer from a bibliometric perspective. Methods: The global literature of MNT on Cancer published between 1975 and 2022 were searched in the Web of Science Core Collection Database (WOSCC). After refining the data, descriptive analysis and data visualization were performed with bibliometric tools (CiteSpace, VOSview, and R package “bibliometrix”). Results: A total of 10,339 documents with a timespan from 1982 to 2022 were included in this study. The number of documents had increased continuously over the past 40 years, especially with a steep rise from 2016 to 2022. The majority of scientific production outputs were from the United States, which had the most core research institutions and authors. The published documents could be clustered into three themes respectively labeled by terms “double-blind”, “cancer” and “quality-of-life”. “gastric cancer”, “outcome”, “inflammation”, “sarcopenia” and “exercise” were the most prominent keywords in recent years. “breast-cancer”, “colorectal-cancer”, “expression”, “risk”, “in-vitro”, “quality-of-life”, “cancer” and “life” might represent the newly emerged topics. Conclusions: There were a good research foundation and reasonable disciplinary structure in the field of medical nutrition therapy for cancer at present. The core research team was mainly located in the United States, England, and other developed countries. According to the current trends in publications, more articles shall be published in the future. Nutritional metabolism, malnutrition risk, and the impact of nutritional therapy on prognosis might be research hotspots. In particular, it was important to focus on specific cancer, such as breast cancer, colorectal cancer, and gastric cancer, which might be the frontiers.